ANALISIS BIAYA PERSEDIAAN BAHAN BAKU IKAN DAN PERHITUNGAN ECONOMIC ORDER QUANTITY (EOQ) PADA RUMAH MAKAN IKAN BAKAR KINAMANG - Wijaya, Melinda Miranda; Saerang, David P. E.; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2018)
The cost of raw material inventory is a sacrifice of economic resources, measured in units of money, which have occurred or are likely to occur for raw material inventory, consisting of purchase costs, storage costs, and inventory shortage. This study aims to determine (1) Total Inventory Cost (TIC) based on RM policy. Kinamang Fuel Fish and Economic Order Quantity (EOQ) method during 2017 (2) Frequency of ordering of efficient fish raw material during 2017 (3) Quantity of safety stock and when to reorder point of raw materials fish in RM. Ikan Bakar Kinamang during 2017. This research is a descriptive research with qualitative approach. And use case study method. The result of the research shows that the Cost of Fish Raw Material Supplies at Kinamang Fuel Fish Restaurant is still not economical because the purchase (order) is only based on the previous sales estimate, and does not take into account economically the expenses incurred for the purchase and storage of fish raw materials the. Precisely with the calculation of Economic Order Quantity (EOQ), the cost of raw materials inventory of fish is much less, and can determine properly and correctly about the safety stock (safety stock), and reorder (reorder point).Keywords: Inventory Cost, EOQ, Frequency, Safety Stock, ROP